SUPPLY CHAIN MANAGEMENT STRATEGY IN SMALL AND MEDIUM ENTERPRISES (SMEs) IN THE CITY OF BANDUNG, WEST JAVA - Maun Jamaludin (Universitas Pasundan, 2021)
This research aims to analyze the SCM strategies that have been implemented by SMEs in Bandung, analyze the SCM strategies used by SMEs and examine various problems and factors that support the success of their implementation.This research uses a qualitative approach, which describes the research problem in a complete and rational manner in accordance with the actual facts and data. The focus of this research is the SCM Strategy, namely determining the SCM strategy for SMEs in Bandung The results of this research prove that the SCM strategy used by SMEs in the city of Bandung in determining suppliers is with a few strategies and many suppliers strategies. The strategy of few suppliers with one supplier is the most widely used strategy by SMEs in Bandung City, while the strategy of using many suppliers is the least strategy carried out by SMEs in Bandung City. In the supply of raw materials for their products, almost all SMEs in the city of Bandung buy their own raw materials. SMEs obtain their raw materials from markets, shops and stalls around their homes. The supply chain management strategy for SMEs in Bandung City is that similar SMEs form cooperatives and will obtain raw materials directly from the company then carry out the manufacturing process (production process) by making products and selling them directly to consumers or selling them to distributors, agents, then to retailers. new retailer to the final consumer.